Additive-Free Copper-Catalyzed Benzylic C(sp3)–H Carbamation: Simple Preparation of Primary Benzylic Amines - Schmidt, William; Bakhoda, Abolghasem (Synlett, 2023)
A simple and practical method for the synthesis of primary alkylamines by direct functionalization of hydrocarbons is described. The N-Boc-protected alkylamines are readily prepared from tert-butyl (trimethylsilyl)carbamate and N-fluorobenzenesulfonimide in the presence of a Cu(I) catalyst at low catalyst loadings. Advantageously, this process proceeds free of any additive such as auxiliary bases/acids, requires only one equivalent of the substrate, and does not require ligand synthesis. This operationally simple C–H carbamation method shows high site selectivity and good functional-group tolerance, and uses a commercially available Cu precatalyst and oxidant to furnish N-Boc protected alkylamines in yields of 16–83%. The products can be simply deprotected under mild acidic conditions to generate primary benzylic amines. This practical method was subsequently used for the synthesis of the active pharmaceutical ingredients cinacalcet and sertraline.
Keywords: copper catalysis; fluorobenzenesulfonimide; amination; alkylamines; benzylic amines